Shortcomings in the JET Programme as a Vehicle for English Pronunciation Teaching by Native Speakers - Brown, Charles Allen (CV. Creative Tugu Pena, 2024)
The Japan Exchange and Teaching (JET) Programme is a longstanding and influential government initiative employing thousands of immigrant teachers throughout Japan. The JET instructional delivery model is characterized by periodic classroom visits from largely untrained English native-speaking teachers who serve as classroom assistants with the licensed teacher – typically a Japanese individual – being in charge. This model was adopted to promote international contact and authentic language exposure with the JET teacher being especially responsible for teaching oral communication. This study focused on empirically examining their pronunciation teaching since there has been little assessment of how the JET instructional delivery model addresses this important dimension of oral communication. To do so, 4879 teaching activities created by JET participants were analyzed in terms of how they addressed critical aspects of pronunciation teaching. Results indicated important shortcomings, including little integration of pronunciation into the curriculum, weak links between listening to notice phonological features and subsequent learner production, poor coverage of the various dimensions of phonology, a lack of attention to assessing learners’ pronunciation needs, and inaccurate presentation of phonology especially through English transcribed into the Japanese katakana writing system. The findings suggest shortcomings inherent in the JET-style instructional delivery model, especially attributable to its recruitment of untrained NS teachers, their sporadic appearance in particular classrooms, and their responsibilities in creating and teaching oral communication lessons. This project is thus important not only within Japan, but also in other contexts where the JET-style model has been embraced as a vehicle for seeking to match native-speaker language skills to student needs. Keywords: English Language Teaching, JET Programme, Katakana English, Native Speaker Fallacy, Pronunciation